Difference equation for a population model - Mami Suzuki (Discrete Dynamics in Nature and Society)
In this paper we consider a difference equation of the form u(t+2)=αu(t+1)+βu(t+1)−αu(t)αu(t), for t>−∞, seems to be a general statement of a relative socio-spatial dynamics. Indeed this equation is one of “population model”. We investigate behavior of solutions and expression of analytic general solutions of this model.